2009
DOI: 10.1897/08-471.1
|View full text |Cite
|
Sign up to set email alerts
|

Leachability of some emerging contaminants in reclaimed municipal wastewater‐irrigated turf grass fields

Abstract: Abstract-Emerging pollutants inherent in reclaimed municipal wastewater, including endocrine-disrupting compounds (EDCs) and pharmaceutical and personal care products (PPCPs), often have cast uncertainties on the safety of water reuse. We examined the fate and transport behavior of several PPCP and EDC compounds through observations made at experimental turf fields irrigated with naproxen, clofibric acid, diclofenac sodium, ibuprofen, estrone, 4-tert-octylphenol, bisphenol A, 4-n-nonylphenol, and triclosan lat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
34
0

Year Published

2010
2010
2017
2017

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 68 publications
(35 citation statements)
references
References 40 publications
1
34
0
Order By: Relevance
“…The results of the present study showed that DOM did not further enhance the release of selected NSAIDs from the soils. The soil K OC values of selected NSAIDs were low, from 100 to 400 cm 3 /g, and thus had relative low affinities with DOM constituents [19,28,29]. A similar trend was observed when the treated soils were extracted by the PAM solution.…”
Section: Water Release Of Nsaids In Soilssupporting
confidence: 58%
See 2 more Smart Citations
“…The results of the present study showed that DOM did not further enhance the release of selected NSAIDs from the soils. The soil K OC values of selected NSAIDs were low, from 100 to 400 cm 3 /g, and thus had relative low affinities with DOM constituents [19,28,29]. A similar trend was observed when the treated soils were extracted by the PAM solution.…”
Section: Water Release Of Nsaids In Soilssupporting
confidence: 58%
“…The sorbed compounds remained on the soil particle surface by electrostatic interactions or entrapped in soil intra-aggregate micropores. Insofar as the preloaded NSAIDs in soil columns were not strongly associated with soil particles (predicted from their K d values in the three soils [28,29]), the initial loading of solution leached out most readily desorbable NSAIDs from soil particles. That may be why the concentrations of NSAIDs sharply decreased after the first pore volume of leachate in ASL columns.…”
Section: Leaching Patterns Of Nsaids From Soil Columnsmentioning
confidence: 95%
See 1 more Smart Citation
“…Today, approximately 50% of U.S. sewage sludge is applied on land as biosolids for inexpensive disposal and as a fertilizer or soil conditioner [101]. The application of biosolids laced with pharmaceuticals can pose secondary risks to water resources via leaching into groundwater and contamination of surface waters from runoff [63,[102][103][104][105].…”
Section: Pharmaceuticals In Municipal Sludgementioning
confidence: 99%
“…Generally, there is a lack of studies on the desorption of ibuprofen in soils. However, scarce studies documented that ibuprofen was mobile in soils with medium to high tendency for leaching to natural waters (Xu et al 2009b;Durán-Álvarez et al 2014) when more than 50% of the total sorbed drug was desorbed.…”
Section: Resultsmentioning
confidence: 99%